Assessment of Selected Barangays in Makati City Towards Improved Barangay Governance - Rosalyn R. Flores (Iapa Proceedings Conference, 2019)
In international development as noted at the Wikipedia, good governance is a subjective term that describes how public institutions conduct public affairs and manage public resources in the preferred way. Governance is the process of decision – making and the process by which decisions are implemented or not. The term governance can apply to corporate, international, national, local governance or to the interactions between other sectors in the society. (1) "What is Good Governance". UNESCAP, 2009. Accessed July 10, 2009. This paper explores the concept of good governance from different perspective that then emerges as a model to compare ineffective economies or political bodies with viable economies and political bodies. The concept centers on the responsibility of governments and governing bodies to meet the needs of the masses as opposed to select groups in society. Because countries often described as most successful are liberal democratic states concentrated in Europe and the Americas( 2) Khan, Mushtaq Husain (2004). State formation in Palestine: viability and governance during a social transformation: Volume 2 of Political economy of the Middle East and North Africa. Routledge. ISBN 978-0-415-33802-8. found at Google Books , good governance standards often measure other state institutions against these states. Aid organizations and the authorities of developed countries often will focus the meaning of “good governance “ to a set of requirements that conform to the organization agenda , making good governance imply many different things in many different contexts. (3) Poluha, Eva; Rosendahl, Mona (2002). Contesting 'good' governance:crosscultural perspectives on representation, accountability and public space. Routledge. ISBN 978-0-7007-1494-0.Thus this paper would adopt the concept of good governance in the Philippine context particularly at the grass root level- the barangay which is considered as the smallest political and yet influential political body in the society. This paper presents the focal area of good governance in terms of delivering public services to the people from different sectors of the society such as Education and Healthcare, Social Protection, Financial Management , Peace and Security, Business Friendliness, Tourism, Environmental Management and Disaster Preparedness.(4) DILG Memorandum Circular No. 2018-194 dated November 6, 2018. There will be some indicators and data requirements in each area of services that would suggest, prove and validate that good governance at the grass root level are met. Through these strategies, the abilities of public sector institutions particularly the barangays in the City of Makati as well as the entire country to deliver key services more effectively and efficiently will be strengthened an these would help a range of public private, civil society partners and stakeholders expand access to and improve the quality of community services.